Adaptation of Three Local Garlics (Allium sativum L.) in Napu Plateau Central Sulawesi. Issue 1 (1st February 2022) - Saidah,; Muchtar,; Wahyuni, A N; Irmadamayanti, A; Risna,; Syafruddin,; Rahayu, Heni S P; Sugito,
Abstract: One of the challenges in developing garlic in Indonesia is increasing its competitiveness. It means that the price and quality must be able to compete with imported garlic. Apart from that, productivity also needs to be increased. Currently, the national demand for garlic is estimated at 539.3 thousand tons per year (2016-2019), where domestic production only reaches 134.7 tons. Therefore, the rest number is fulfilled by importing. This condition has spurred many parties to take part in supporting the garlic development program, including the Central Sulawesi provincial government. Napu Plateau in Poso District Central Sulawesi Province is an area above 1000 meter of sea level and has A rain type with agro-climatic zone A1. This condition is very suitable for the development of vegetable crops, including garlic. The research objective was to determine the adaptability of three local varieties of garlic. The activity was carried out in Watumaeta Village, North Lore Subdistrict, Poso District, Central Sulawesi in April-July 2020. The study used a Randomized Block Design with treatments of three local varieties of garlic, namely Lumbu Hijau, Sembalun and Tinombo. Number of repetitions were five units. Observed parameters included plant height, number of leaves and stem diameter, bulb diameter, bulb weight, and number of cloves. The results showed that the garlic varieties have no significant effect on all observed parameters, except stem diameter, bulb dry weight and number of cloves. Those three local varieties have average number 54, 70-58, 18 cm of plant height; 7, 70-8, 08 of leaves; 0, 35-0, 42 cm of stem diameter; 2, 41-2, 78 cm of cloves diameter; bulb dry weight 11, 92-17, 09 gram; 4, 10-4, 90 of number of cloves. Among the three local varieties, Tinombo from Parigi Moutong District was superior compare to the other two varieties.